EKRANISASI UNSUR NARATIF WEBTOON "THE SECRET OF ANGEL" KE DALAM DRAMA "TRUE BEAUTY": IMPLIKASI TERHADAP MATERI PEMBELAJARAN BAHASA KOREA - Khairunisa Salwa Salsabila, - (2022)
This study aims to determine the narrative elements of each webtoon in order to determine the ecranization that occurred and to find out the factors that influence the occurrence of the ecranization. In the analysis process, the author uses Eneste's theory (1991) in Alfian (2014) related to ecranization, Eriyanto's (2013) theory related to narrative elements, and Pratista's (2017) theory related to factors that influence the occurrence of ecranization. This study uses a qualitative method with a descriptive approach. The results of this study indicate that there is a reduction, addition, and changes. Shrinking is the form of trimming stories and plots in the story, such as trimming episodes where the webtoon consists 135 episodes while the drama consists 16 episodes, thus plot trimming where in the drama there are only 9 conflicts while in the webtoon there are 12. Other than that, there is an addition to the story and the characters, where in the drama Ju Kyung's family background and the father figure are told in sufficient detail, while in the webtoon until episode 135, the father figure never appears. Last but not least, changes occur in the story. The plot and setting where the webtoon version focuses more on how to have an external appearance that is in accordance with Korean society's beauty standards, the drama version "True Beauty" emphasizes that True Beauty comes from the inside. So it could be concluded in this research that there is an ecranization of narrative elements in the form of reduction, addition, and changes in terms of the story, plot, characters and setting.